Implementasi Sistem Absensi Siswa Berbasis Deteksi Wajah, Warna Dan Logo Seragam - Asrul Asrul (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Uniform is one of the driving factors to improve student discipline. The current problem is that checking uniforms and attendance to improve student discipline is still done manually. In previous studies, the attendance system only detected the face, which means that it was not able to detect the uniform color used by students and also the logo as the identity of student uniforms. Thus, they could freely use any uniform when entering the classroom. This study aims to update the manual attendance system to the computer by detecting facial parts and uniform colors and logos. Faces that have been previously recorded and stored in a database are then used to detect faces which are then compared with faces in the database and recognize uniform colors and logos. The method used for this research is the ViolaJones method which functions to detect facial parts. Meanwhile, the RGB color Thresholding method is used to detect a uniform color, and the Template Matching Algorithm is used to detect a uniform logo. The best results are obtained from testing with a distance parameter of 50 cm and an accuracy level of 92.9%. The time required is 2.2 seconds using a 2 MP camera.